Chasing Hillary ten years, two presidential campaigns, and one intact glass ceiling - Chozick, Amy (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2018)
"The dishy, rollicking, and deeply personal story of what really happened in the 2016 election, as seen through the eyes of the New York Times reporter who gave eight years of her life to covering the First Woman President who wasn't."--
"For nearly a decade, award-winning New York Times journalist Amy Chozick chronicled Hillary Clinton's pursuit of the presidency. Chozick's assignments, covering Clinton's imploding 2008 campaign and then her front-row seat to the 2016 election on "The Hillary Beat," set off a years-long journey in which the formative years of Chozick's twenties and thirties became, both personally and professionally, intrinsically intertwined with Clinton's presidential ambitions. As Clinton tried, and twice failed, to shatter "that highest, hardest glass ceiling," Chozick was trying, with various fits and starts, to scale the highest echelons of American journalism. In this rollicking, hilarious narrative, Chozick takes us through the high- (and low-) lights of the most noxious and dramatic presidential election in American history. Chozick's candor and clear-eyed perspective--from her seat on the Hillary bus and reporting from inside the campaign's Brooklyn headquarters to her run-ins with Donald J. Trump--provide fresh intrigue and insights into the story we thought we all knew. This is the real story of what happened, with the kind of dishy, inside details that repeatedly surprise and enlighten. But Chasing Hillary is also the unusually personal and moving memoir of how Chozick came to understand Clinton not as an unknowable enigma and political animal, but as a complete, complex person, full of contradictions and forged in the crucible of political battles that had long predated Chozick's years covering her. And as Chozick gets engaged, married, buys an apartment, climbs the professional ladder, and inquires about freezing her eggs so she can have children after the 2016 campaign, she dives deeper into decisions Clinton had made at similar points in her early career. In the process, Chozick develops an intimate understanding of what drives Clinton, how she accomplished what no woman had before, and why she ultimately failed. Chozick also reveals how the social fissures in the electorate that drove angry voters to Trump and blindsided Clinton would unexpectedly bring out the tensions in Chozick's own life--between the red state she came from and the blue state she ended up in, and her desire to climb in her career as a woman but be treated no differently than a man. Clinton's shocking defeat would mark the end of the almost imperial hold she'd had on Chozick for most of her professional life. But the results also make Chozick question everything she'd worked so hard for in the first place. Political journalism had failed. The elite world Chozick had tried for years to fit in with had been rebuffed. The less qualified, bombastic man had triumphed (as they always seem to do), and Clinton had retreated to the woods in Chappaqua, finally comfortable enough to just walk, no makeup, no pants suit, showing the real person Chozick had spent years hoping to see. Illuminating, poignant, laugh-out-loud funny, Chasing Hillary is a campaign book unlike any other that reads like a fast-moving political novel."--Dust jacket.
Happy Hillary -- Jill wants to see you -- "The world's saddest word" -- Bill Clinton Kaligani -- Roving -- The foreign desk -- "Scoops of ideas" -- "Taking back America" -- Leave Hillary alone -- "Iowa ... I'm baaack" -- The last good day -- Emailghazi -- "What makes you so special?" -- The everydays -- "Fucking Democrats" -- The ninnies -- A tale of two choppers -- Sorry, not sorry -- The pied piper -- "Spontaneity is embargoed until 4:00 p.m." -- "Schlonged" -- "I am driving long distances in Iowa and may be slower to respond" -- Meeting our Waterloo -- The girls on the bus -- You will look happy -- He deprived her of a compliment -- "Saint Hillary" -- I hate everyone -- "You should be so pretty!" -- Prince Harry -- The plane situation -- The gaffe tour -- "Let Donald be Donald" -- Stay just a little bit longer -- The kids are alright -- Writing herstory -- Who let the dog out? -- "Man, y'all are jittery" -- The bed wetters -- Off the record ... until hacked -- The red scare -- Gladiator arena -- "HRC has no public events scheduled" -- "Media blame pollen" -- The fall of magical thinking -- Debate Hillary -- How I became an unwitting agent of Russian intelligence -- The "big ball of ugly" -- Bill's last stand -- Chekhov's gun -- Hillary's death march to victory -- The tick-tock number one -- The tick-tock number two -- The morning after.
106084
Keywords: Clinton, Hillary Rodham; Chozick, Amy; Presidential candidates -- United States -- Biography; Presidents -- United States -- Election -- 2016.; Presidents -- United States -- Election -- 2008.; Women journalists -- United States -- Biography; Biography & Autobiography -- Personal Memoirs; Biography & Autobiography -- Political; Political Science -- Political Process -- Campaigns & Elections; United States -- Politics and government -- 21st century; Biographies